Morphometry MRI in the differential diagnosis of parkinsonian syndromes Morfometria por ressonância magnética no diagnóstico diferencial das síndromes parkinsonianas - Rômulo L Gama; Daniel F.G Távora; Rodrigo C Bomfim; Cruiff E Silva; Veralice M. de Bruin; Pedro F. de Bruin (Arquivos de Neuro-Psiquiatria, 2010)
This study evaluates the diagnostic value of morphometric magnetic resonance imaging (MRI) in the differential diagnosis among Parkinson's disease (PD), progressive supranuclear palsy (PSP) and multiple system atrophy (MSA). We studied 21 PD cases, 11 MSA-c, 8 MSA-p and 20 PSP cases. Midbrain area (Ams), pons area (Apn), middle cerebellar peduncle (MCP) and superior cerebellar peduncle (SCP) were measured using MRI. Comparisons were made between PD, MSA-p, MSA-c and PSP. Apn, MCP and SCP morphometry dimensions presented differences among groups. Ams below 105 mm² and SCP smaller than 3 mmwere the most predictive measures of PSP (sensitivity 95.0 and 80.0%, respectively). For the group of MSA-c patients, Apn area below 315 mm² showed good specificity and positive predictive value (93.8% and 72.7%, respectively). In conclusion, dimensions and cut off values obtained from routine MRI can differentiate between PD, PSP and MSA-c with good sensitivity, specificity and accuracy. Morfometria pela ressonância magnética (RM) no diagnóstico diferencial entre doença de Parkinson (DP), paralisia supranuclear progressiva (PSP) e atrofia de múltiplos sistemas (AMS). Este estudo avaliou a RM no diagnóstico diferencial de 21 casos com DP, 11 AMS-c, 8 AMS-p e 20 com PSP. A área sagital do mesencéfalo (Ams), área sagital da ponte (Apn), largura do pedúnculo cerebelar médio (PCM) e pedúnculo cerebelar superior (PCS) foram medidas pela RM e realizadas comparações entre destes pacientes. A Ams <105 mm² e a largura média do PCS <3 mm foram preditivas para PSP (sensibilidade de 95,0 e 80,0%, respectivamente). Nos casos de AMS-c a área pontina <315 mm² apresentou boa especificidade e valor preditivo positivo para o diagnóstico (93,8% e 72,7%). Em conclusão, as dimensões e valores de cortes obtidos a partir da RM podem diferenciar PD, PSP e AMS-c, com sensibilidade, especificidade e precisão.